Deciphering exciton-generation processes in quantum-dot electroluminescence - Yunzhou Deng (Nature Portfolio, 2020)
Today it remains unclear how excitons are electrically generated in individual nanocrystals. Here, the authors propose the identification of the longlived intermediate QD– state for exciton generation of CdSe-based QD-LEDs by a room temperature electrically-pumped single-molecule spectroscopy.